Pengetahuan Ibu Hamil Tentang Perubahan Psikologi Dalam Kehamilan Di Klinik - Vivi Octapiya; Sri Legawati (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
Based on WHO data, there were 352 people out of 2,321 primigravida pregnant women who complained of fear 36%, anxiety 42%, lack of confidence 22% during pregnancy. This data is also supported by the results of the Indonesian Demographic Health Survey (SDKI), there were 50 people out of 850 primigravida pregnant women who complained of stress 20%, anxiety 35% and fear 45% during pregnancy. Meanwhile, according to the Medan Ministry of Health in 2009, there were 25 people out of 100 pregnant women who complained of anxiety 70%, fear 25%, and stress 5%. The purpose of this study was to determine the knowledge of pregnant women about psychological changes during pregnancy in the independent practice of midwife Eliza Bestari Sinaga Gambir Baru Asahan. The research method was descriptive quantitative with a cross-sectional approach. The research location was at the Independent Practice of Midwife (PMB) Eliza Bestari Sinaga Gambir Baru Asahan. The research sample used a saturated sampling technique. The sample in this study consisted of 10 pregnant women visiting the Eliza Bestari Prenatal Care Center (PMB). A closed-ended questionnaire was used as data collection tool, while frequency distribution was used for data analysis. The results showed that the majority of pregnant women's knowledge regarding psychological changes during pregnancy was considered quite good (63%). Seven respondents (70%) were aged 21-25, five respondents (50%) had a bachelor's degree, and four respondents (40%) were housewives. The conclusion of this study indicates that the majority of pregnant women's knowledge regarding psychological changes during pregnancy was quite good.